The Complement System and ANCA Associated Vasculitis in the Era of Anti-Complement Drugs - Kimoto, Yasutaka; Horiuchi, Takahiko (Frontiers in Immunology, 2022)
ANCA (anti-neutrophil cytoplasmic antibody)-associated vasculitis (AAV) is the condition in which ANCA, as an autoantibody, is associated with the pathogenesis of vasculitis in small blood vessels, mainly in the ear, nose, throat, kidney, lung, and nerves. These diseases are important because they can be fatal due to renal failure and pulmonary hemorrhage if not promptly and appropriately treated. Recently accumulated evidence has shown that C5a produced by the complement alternative pathway primes neutrophils, which in turn activate the complement alternative pathway, leading to the pathogenesis of AAV. Avacopan (CCX168), a C5aR antagonist was shown to be effective against AAV, and it has been a novel therapeutic option, becoming a novel anti-complement drug to modulate inflammatory diseases.